Assessment of the impact of a multidisciplinary clinic for new babies with cleft lip and/or palate. (29th September 2015) - Mansour, M; Drake, D; Scholler, I; Rogers, W; Wooldridge, M; Rowe, M; Phillips, L; Barrett, J; Peters, S; Thain, H
Abstract : Aims: The aims of this survey were firstly to determine the work of a Multidisciplinary New Baby Clinic for infants with cleft lip and/or palate. Secondly to compare our clinic setup with other cleft centres in the UK and Ireland. Methods: A retrospective review was undertaken of case notes and correspondences regarding all of the 79 new patients seen in the first 21 months since paediatricians joined the multidisciplinary team in March 2007. In addition, in December 2008, a telephone questionnaire was held with representatives from all the other cleft centres, to establish if they had New Baby Clinics, and if so, how these clinics were organised. Results: All babies underwent a full examination and an echocardiogram in clinic. In the cohort of patients studied, 16.5% had clinically important cardiac abnormalities and approximately 20% had other comorbidity; some abnormalities had been detected at birth, prior to the clinic visit. Involvement of local paediatricians in following up infants born with clefts rose from 30% to 93%. Only two other cleft centres had paediatricians in their multidisciplinary clinics. In most other centres, babies were assessed preoperatively on the ward by a paediatrician or a trainee, and paediatric follow-up was not usually arranged, unless there were obvious associated anomalies. Conclusions: The New Baby Clinic in our region is one of only three in the UK and Ireland with paediatricians present, and the only one with an anaesthetist. This makes it ideally placed to identify medical problems promptly, and provide solutions well in advance of the time of cleft surgery. In addition, since March 2007, referrals from our New Baby Clinic resulted in a considerable rise in the involvement of local paediatricians in the follow-up of a population of infants well-documented to have increased probability of comorbidity. This model of care may help to provide a more holistic approach of continued developmental and medical assessments, and early management of issues that may impact on long-term outcome.